A constraint-based morphological analyzer for concatenative and non-concatenative morphology - Roxas, Rachel Edita O. (Animo Repository, 2006)
Morphological analysis in the current methods, such as finite-state and unification-based, are predominantly effective for handling concatenative morphology (e.g. prefixation and suffixation), although some of these techniques can also handle limited non-concatenative phenomena (e.g. infixation and partial and full-stem reduplication). A constraint-based method to perform morphological analysis that handles both concatenative and non-concatenative morphological phenomena is presented, based on the optimality theory framework and the two-level morphology rule representation. Although optimality theory has been proven effective in handling non-concatenative phenomena, it has been applied for the generation process, and in this study, it has been shown to be effective also in morphological analysis. The method was tested on 1,600 Tagalog verb forms (having 3 to 7 syllables) from 50 Tagalog roots which exhibit both concatenative and non-concatenative morphology. The resulting method is able to produce the correct underlying forms of the surface forms of 96% of the test data, having a 4% error, which is attributed to d-r alternation.